2020
DOI: 10.1021/acs.iecr.0c04546
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the Shuttling of Polysulfide by a Self-Assembled FeOOH Separator in Li–S Batteries

Abstract: Fabrication of a functional separator with physical methods such as slurry casting and vacuum filtration method is a common way to capture the dissolved polysulfide and suppress its shuttling in lithium−sulfur batteries (Li−S battery). However, most of the layers are covered on the PP separator by weak physical adhesion, and it is hard to guarantee stability during longterm cycling at high rates. Therefore, we take advantage of the strong oxidization of acidic ferrate solution and design a novel simple chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…TG analysis of ASR (Figure 3A) showed that the thermal degradation of ASR can be divided into two stages. At the temperature below 170°C, the weight loss (about 1%) at early stage was mainly caused by the moisture evaporation of ASR 36 . The first stage of ASR degradation occurred in the temperature range of 226–306°C, with a weight loss of about 7.5%, which was mainly attributed to the degradation of PVC.…”
Section: Resultsmentioning
confidence: 99%
“…TG analysis of ASR (Figure 3A) showed that the thermal degradation of ASR can be divided into two stages. At the temperature below 170°C, the weight loss (about 1%) at early stage was mainly caused by the moisture evaporation of ASR 36 . The first stage of ASR degradation occurred in the temperature range of 226–306°C, with a weight loss of about 7.5%, which was mainly attributed to the degradation of PVC.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the slow diffusion rate of LiPSs to the active surfaces and the limited accessible surfaces of catalyst would severely impair catalytic reaction efficiency if the catalytic active substances are not sufficiently downsized. Therefore, elevating the utilization of active catalytic sites and improving LiPS surface diffusion properties through uniform nanometer-scale distribution or even atomic-scale distribution is another significant criterion for catalyst introduction in Li–S battery systems. , Recently, transition-metal oxyhydroxides (e.g., CoOOH, FeOOH, and NiOOH), which have similar structural composition to transition-metal oxides/hydroxides, have been proved advantageous to ameliorate the kinetics and improve the electrochemical performances of Li–S batteries. , Especially, β-Nickel oxyhydroxide (β-NiOOH) is one of the promising transition-metal oxyhydroxide catalysts. Benefiting from the analogous structural composition with NiO and Ni­(OH) 2 , β-NiOOH possesses similar catalytic activity and homologous strong polarity for anchoring LiPSs .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their chemical stability, high abundance, low cost, and eco-friendly nature, iron-based materials attract tremendous attention. Iron oxide-hydroxide (FeOOH), as an important naturally occurring form of iron, is widely present in environmental media such as soil, water sediments, and mine wastewater . FeOOH has been widely applied in electrode materials, ,, adsorption of harmful ions, , and degradation of organic pollutants , because of its high specific capacity, large specific surface area, as well as the high density of surface hydroxyl groups. However, its application in organic synthesis catalysis is rarely reported.…”
Section: Introductionmentioning
confidence: 99%